Perencanaan Ulang Perkerasan Lentur Untread Base Pada Jalan Sumber Cangkring - Wonojoyo Kecamatan Gurah Kabupaten Kediri - Indah Handayasari; Agnes Paradiana Putri (Sekolah Tinggi Teknik - PLN, 2016)
Flexible pavement with Cement Treated Base is a flexible pavement that use cement as a binder base course on. One of the roads that use a flexible pavement with Cement Treated Base Jalan Source Cangkring - Wonojoyo Gurah District of Kediri. But the application of pavement Cement Treated Base on the road section Source Cangkring - Wonojoyo need for reconsideration in view of these roads are local roads that have traffic volume is very low. In this study, flexible pavement with Cement Treated Base will be redesigned using flexible pavement with untreated Base Component Analysis Method of Highways. Based on the thickness of flexible pavement design calculation Base untreated gained 5 cm thick surface layer, layers of foundation over 20 cm and 10 cm below the base course. While the cost calculation, untreated flexible pavements Base requires a budget of Rp 1,584,452,093.92 and flexible pavement with Cement Treated Base requires a budget of Rp 1,889,041,526.00 by a margin of 16.12% on the same road. Judging from the results of the calculation, flexible pavements Base untreated cheaper and more effective for class III roads such as the road-Wonojoyo Source Cangkring Gurah District of Kediri.